Gerontology - D'Onofrio, Grazia; Greco, Antonio; Sancarlo, Daniele (IntechOpen, 2018)
Aging well and actively is the real objective of human being. This book is an up-to-date and realistic view on physiopathological mechanisms of aging and age-related diseases. The book includes topical contributions from multiple disciplines to support the fundamental goals of extending active life and enhancing its quality.